Long-Lasting Cranial Nerve III Palsy as a Presenting Feature of Chronic Inflammatory Demyelinating Polyneuropathy - Rossella Spataro; Vincenzo La Bella (Case Reports in Medicine)
We describe a patient with chronic inflammatory demyelinating polyneuropathy (CIDP) in which an adduction deficit and ptosis in the left eye presented several years before the polyneuropathy. A 52-year-old man presented with a 14-year history of unremitting diplopia, adduction deficit, and ptosis in the left eye. At the age of 45 a mild bilateral foot drop and impaired sensation in the four limbs appeared, with these symptoms showing a progressive course. The diagnostic workup included EMG/ENG which demonstrated reduced conduction velocity with bilateral and symmetrical sensory and motor involvement. Cerebrospinal fluid studies revealed a cytoalbuminologic dissociation. A prolonged treatment with corticosteroids allowed a significant improvement of the limb weakness. Diplopia and ptosis remained unchanged. This unusual form of CIDP presented as a long-lasting isolated cranial nerve palsy. A diagnostic workup for CIDP should therefore be performed in those patients in which an isolated and unremitting cranial nerve palsy cannot be explained by common causes.